Study of 6-propyl-2-thiouracil as a radioprotector for the thyroid gland - Perona, Marina (2010)
The objective of the paper was to study the application of 6-propyl-2-thiouracil (PTU) as a radioprotector for the thyroid gland. Rat thyroid epithelial cells (FRTL-5) and human colon cancer cells (ARO81-1) were exposed to γ-irradiation with or without 1 mM PTU. Radiation response was analysed by clonogenic survival assay. Cyclic AMP levels were measured by Radioimmunoassay (RIA). The results showed that PTU increased the Surviving Cell Fraction (SF) at 2 Gy significantly (p < 0.05) in both cell lines. PTU increased extracellular levels of cAMP in all the treatments in a dose- and time-dependent manner for FRTL-5 cells. In ARO81-1 cells, a peak was observed at 24 hours in extracellular levels incubated with 1 mM PTU (36.97 ± 6.74 fmol/μg prot vs. control: 17.53 ± 3.9 fmol/μg prot, p < 0.001). Forskolin and dibutyril cAMP mimicked the effect of PTU on SF. Thus PTU appears to be a radioprotector for thyroid cells and could exert its effect through cAMP.